2021
DOI: 10.1155/2021/3711699
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Nursing Intervention Can Improve Dysphagia and Quality of Life of Patients Undergoing Radiotherapy for Esophageal Cancer

Abstract: Objective. To seek the improvement of rehabilitation nursing intervention on dysphagia and quality of life of patients with esophageal cancer undergoing radiotherapy. Methods. A total of 109 patients with esophageal cancer undergoing radiotherapy were selected as research objects. According to the random number table, they were separated into the control group (CG) and intervention group (IG), with 45 cases in CG and 64 cases in IG. In CG, patients were given routine nursing intervention, while those in IG wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…As reported previously, a significant negative correlation was observed between perceived stress level and overall QOL. [ 18 , 20 , 22 , 23 ] Some studies have reported that various sociodemographic variables affect the QOL of patients with gastrointestinal corrosive injuries. On the other hand, a significant sex difference was found in the psychological aspect of QOL, with men scoring higher than women in this study.…”
Section: Discussionmentioning
confidence: 99%
“…As reported previously, a significant negative correlation was observed between perceived stress level and overall QOL. [ 18 , 20 , 22 , 23 ] Some studies have reported that various sociodemographic variables affect the QOL of patients with gastrointestinal corrosive injuries. On the other hand, a significant sex difference was found in the psychological aspect of QOL, with men scoring higher than women in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic and standardized management of patients with esophageal cancer undergoing chemotherapy can meet the nursing requirements at all stage of chemotherapy. At the same time, paying attention to individualzed nursing, strengthens psychological nursing, improving patients’ compliance with treatment, and having strong clinical applicability are of great significance to ensure the normal progress of patients’ chemotherapy ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies on psychological interventions to help patients have been reported. For example, psychological interventions have significant clinical efficacy on recovery and improvement of life quality in esophageal cancer patients [ 15 ]. Hadlandsmyth et al reported a single psychological intervention for women undergoing breast cancer surgery and found that it posed some small positive effects on postsurgical pain and anxiety [ 16 ].…”
Section: Introductionmentioning
confidence: 99%